Development of stable colorant from the anthocyanin-based aqueous extract of sweet potato (Ipomoea batatas L.) leaves - Pagulayan, Jin Mark dG
The study aimed to develop a stable food colorant from the aqueous anthocyanin-based extract of Inubi and red sweet potato (Ipomoea batatas L.) leaves (SPL). Specifically, the study: (a) evaluated the effects of raw material weight (RMW) and boiling time (BT) on the total soluble solids (TSS), instrumental color and consumer acceptability scores of sweet potato leaf colorants (SPLC) using central composite rotatable response surface methodology; (b) established the optimum parameters for SPLC extraction using the validated optimization models; and (c) determined the total phenolic content (TPC), total antioxidant capacity (TAC), potential food applications, and effect of pH and different acids (i.e. lactic acid, citric acid, and phosphoric acid) on the optimized SPLC. It was found that RMW and BT generally had a significant (p<0.05) effect on the TSS, instrumental color and consumer acceptability scores of the two varieties of SPLC. The optimized parameters for Inubi and red SPLC extraction were found to be 34.47-72.03 g of leaves per 500 mL water boiled for 27.50-30.44 min and 34.47-87.50 g of leaves per 500 mL boiled for 2.75-27.50 min, respectively. Verification studies found that the developed statistical models were accurate in predicting the responses for the study. The optimized SPLC had a TPC of 0.0652-0.0014 mg GAE/mL and TAC of 0.09-0.20 mg TE/mL. Color parameters (i.e, lightness [L*] and chroma [C*] values) of the optimized SPLC decreased as pH increased. The type of acid affected L* due to differences in the volume of acid added to adjust to the desired pH. Colors produced by the two SPLC ranged from red, brown, green, yellow, violet, and blue at varying pH. Initial findings on the utilization of SPLC showed its potential as a natural colorant for some food items including sorbets, cocktail mixes and flavored jelly.